1998
DOI: 10.1029/98ja02749
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of equatorial F region irregularities: Evidence for tropospheric seeding

Abstract: Based on the experiments we consider, we predict that the s/1 variations of Pseed will be found to be similar to those of PEF•, and largely to explain them. Finally, we find reasons, based on the similarity of the DRSF variations to s/1 patterns of the average scintillation index, for not using, as is commonly done, such scintillation patterns as substitutes for PEF• or Pinst patterns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
233
2

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(253 citation statements)
references
References 39 publications
18
233
2
Order By: Relevance
“…Providing a full explanation of these deviations from model predictions greatly exceeds the scope of this observational report. However, the role of interhemispheric winds in suppressing EPB activity has been discussed in the literature (Mendillo et al, 1992;Kil and Heelis, 1998) and can easily be compared with data shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Providing a full explanation of these deviations from model predictions greatly exceeds the scope of this observational report. However, the role of interhemispheric winds in suppressing EPB activity has been discussed in the literature (Mendillo et al, 1992;Kil and Heelis, 1998) and can easily be compared with data shown in Fig. 3.…”
Section: Discussionmentioning
confidence: 99%
“…The Tsunoda model addresses effects of systematic variations in Pedersen conductance and Sq-generated electric fields in the dusk sector. Random events, such as sporadic E layers (Whitehead, 1970;Stephan et al, 2002) and gravity waves (McClure et al, 1998;Singh et al, 1997), act to suppress and stimulate EPB formation, respectively. The magnetic storm of 6 November 2001 illustrates two related random aspects of EPB formation.…”
Section: Discussionmentioning
confidence: 99%
“…Kil and Heelis, 1998). McClure et al (1998) proposed the importance of gravity waves to initiate the R-T instability process.…”
Section: Fe Pmentioning
confidence: 99%
“…Several investigators (e.g. Rottger, 1977Rottger, , 1981McClure et al, 1998) have studied the initiation of ESF related to the tropospheric disturbance sources. Also, several investigators (e.g.…”
Section: Observations Of Plasma Bubbles During Low Spread-f Seasonmentioning
confidence: 99%